Patterns of constitutional design the role of citizens and elites in constitution-making - Wheatley, Jonathan 1964-; Mendez, Fernando 1972- (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2013)
Bridging the gap between law and political science this book draws together divergent research on the role of constitution making in conflict resolution, constitutional law and democratization and employs a wide variety of qualitative and quantitative methods to unfold and explore the political frameworks of the states affected